Dimensions of systems and transformations: A scoping method for transitions case studies - Jonathan Hugh Köhler; Jakob Edler; Katharina Schiller; Sven Wydra (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2025)
There is a need for concepts and methods to develop generic insights across cases in transitions studies based on thorough and systematic empirical analysis. Based on the major strands of transition literature, this paper develops dimensions for a socio-technical system level analysis, differentiating between dimensions of the system under study and its dynamic dimensions of change and illustrates their application to compare cases and identify possible entry points for analysis. System dimensions are grouped into the function and sectors of the system, its characteristics, including context, actors and power structures. Transformation dimensions address the societal need (the wicked problem) drivers and barriers, politics and dynamics of the system. We suggest questions to help in starting an analysis of the dimensions. An illustration for the German bioeconomy gives an example of how to draw general conclusions as to the value of a structured systems and transformation analysis to support policy understanding and practice.
Keywords: 330; System dimensions; transformation dimensions; analytical framework; transitions case study